Beyond dichotomies, in the search for a democratic dialogue toward social-ecological care: Lessons from the Simeto River Agreement in Sicily, IT - Pappalardo, Giusy; Gravagno, Filippo (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2018)
In contemporary societies, environmental and social crises arise as two faces of the same coin, in concert with the crisis of current democratic systems. Innovative forms of democratic governance are needed for facing these crises. This requires the search for a common path between self-organized communities and institutions toward more responsible and effective actions for taking care of social ecological systems. How can this be done, in contexts where communities and institutions do not have a strong background of collaborative practices? This paper reflects on a process that has been set up since 2008 by the XXXX of the University of XXXXX and developed thanks to a specific approach to the institutional academic Third Mission, inspired by the paradigms of action research. The process has been conducted through a long-term university-community partnership. Regardless of various phases of conflict, the partnership built a dialogical relationship with institutions at various levels, ending up in 2015 in an ongoing experiment, the Simeto River Agreement, in Eastern Sicily, IT. Nelle società contemporanee, le crisi ambientali e sociali possono essere lette come due facce della stessa medaglia, in relazione con la crisi degli ordinamenti democratici attuali. Per superare tale condizione, è oggi necessario sperimentare nuove forme di governance basate su percorsi condivisi tra comunità auto-organizzate e istituzioni per produrre azioni responsabili ed efficaci nella tutela dei socio-ecosistemi. Come far sì che ciò accada, in contesti dove comunità e istituzioni non hanno alle spalle un'attitudine consolidata a intraprendere percorsi collaborativi? Il paper propone alcune riflessioni che emergono da un processo avviato nel 2008 dal XXXXX dell'Università di XXXX e alimentato mediante uno specifico approccio alla Terza Missione universitaria, ispirato ai paradigmi della ricerca azione. Il processo è stato condotto attraverso una partnership di lungo termine con la comunità della Valle del Simeto (Sicilia Orientale). Nonostante diverse fasi di conflitto, la partnership ha costruito una relazione dialogica con le istituzioni – a vari livelli – esitando nel 2015 in una sperimentazione in corso, il Patto di Fiume Simeto.